Pregled stanja privatnog šumoposjeda u Republici Hrvatskoj - Paladinić, Elvis (Array, 2008)
Summary: Private forests and private forest ownership has to be reconsidered under the light of changed relationships and the ongoing process of restitution. State of private forestry in Croatia as one of the transition countries, is characterized by small property size, huge number of owners and modest level of organisation. At the same time this sector is characterized by numerous changes and noticeable development. The newly established Extension service for private forest owners under the Ministry of Regional Development, Forestry and Water Management brought private forestry into the focus, providing information, education, help and fresh ideas to the private forest owners. Results of their activities can be seen through highly increased number of private forest owners' associations and their slightly changed attitudes towards their forest property. In the future, the importance of this service can only grow because of its linking position in many processes connected to the accession to the European Union or in using the pre-accession funds. This paper also presents the main characteristics of private forest owners, their respective forest properties, state of their organisation and relating legislative